Designing the Distribution Route for 40 Kg Cement Using Ant Colony Optimization Algorithm at PT. SBI Tuban - Rusindiyanto; Yekti Condro Winursito; Isna Nugraha; Hafid Syaifullah; Mochammad Dicky (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
Distribution is a process of distributing goods or services needed from producers or service producers to consumers and to users, wherever and whenever needed. Problems that often occur in the distribution process that are often encountered are constraints on ineffective routes and inadequate fleet carrying capacity, especially in the Tuban and surrounding areas. This study aims to optimize the distribution route using the Ant Colony Optimization algorithm. This method is used to determine the shortest route that can be taken with the help of ants, achieving optimal results in reducing the distance. The conclusion from this research is that the route, namely the total distance traveled for the ant colony algorithm is 163.2 km for one trip. The fleet required for each shipment is 2 trucks with each truck carrying 8 tons and 7.6 tons. And each truck covers a round trip distance of 151.7 km and 61.7 km.